2015
DOI: 10.1111/cup.12633
|View full text |Cite
|
Sign up to set email alerts
|

Indolent CD8‐positive lymphoid proliferation of acral sites: three further cases of a rare entity and an update on a unique patient

Abstract: Indolent CD8-positive lymphoid proliferation of acral sites is a distinctive and readily identifiable entity and should be included in the next consensus revision of cutaneous lymphoma classification. Although cases described thus far have followed an indolent clinical course, dermatologists should remain guarded about the prognosis and full staging and longitudinal observation are recommended until this condition is better understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…2 We report the first case of treatment by Mohs micrographic surgery. Treatment options have included careful clinical surveillance, corticosteroids, radiotherapy, and surgical excision.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…2 We report the first case of treatment by Mohs micrographic surgery. Treatment options have included careful clinical surveillance, corticosteroids, radiotherapy, and surgical excision.…”
Section: Discussionmentioning
confidence: 93%
“…2 Despite this increase in the number of reported cases, the diagnosis is not yet recognized in the (2005) WHO/EORTC classification. A recent review article identified a total of 23 case reports or series, totaling 51 patients with CD8-positive lymphoid proliferations of acral sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations